Methodological Aspect of the Legal Facts Theory - Shafalovich, Hanna (Teisė, 2021)
This article explores innovations in the methodology and methods in the research of the legal facts theory. It substantiates the historical and theoretical approach for studying the theoretical achievements of legal systems of the past and the methodology of “mechanical” and “quantum-physical” jurisprudence for studying the theoretical achievements of modern jurisprudence.